Discharge against medical advice in pediatrics: a 10-year retrospective analysis in a tertiary care center - Mohammed Albalawi; Kim Sadler; Gassan Abudari; Raghad Tariq Alhuthil; Hamad Hussain Alyami; Atheer Hani Alharbi; Rakan Hazem Badran; Abdulaziz Omar Balhmar (Annals of Saudi Medicine)
BACKGROUND: There is still limited data on Discharge Against Medical Advice (DAMA) in the pediatric population. Most research comes from low—and middle-income countries, where the financial burden associated with medical care is often an important reason to leave a healthcare facility prematurely. Discharge against medical advice in the children's population is considered a significant issue that may lead to an increased risk of morbidity and mortality. OBJECTIVES: Describe the characteristics and predictors of DAMA in children over ten years in in Riyadh, Saudi Arabia. DESIGN: Retrospective SETTING: Tertiary care center. PATIENTS AND METHODS: This study included all patients aged <14 years who had DAMA during all admissions between 1 January 2012, and 31 December 2022. MAIN OUTCOME MEASURES: Data was retrieved from medical records and included 1) sociodemographic data, 2) medical history and clinical characteristics, 3) utilization of services during the admission leading to DAMA, and 4) interventions provided to prevent departure. SAMPLE SIZE: 355 DAMA episodes. RESULTS: Males accounted for 45.4%, and the average age was 4.4 years. The overall DAMA prevalence of was 0.4%. At baseline, 277 children (78%) had at least a chronic illness or severe baseline condition; 59% had a potential life-limiting or life-threatening condition. Reasons for DAMA included disagreement about the treatment plan (14.9%), social reasons (12.6%), and perception that the child's condition improved (5.6%). An increased risk of DAMA recurrence was associated with pre-existing severe or chronic medical conditions (OR: 8.2, P=.004) and a discharge during the treatment phase (OR: 1.9, P=.040). CONCLUSIONS: Despite inconsistent documentation, preventive measures included the involvement of healthcare providers, social services, and patient relations. The study highlights the need for standardized protocols and improved documentation practices to effectively address discharge against medical advice. LIMITATIONS: Needs to moderate documentation quality of DAMA episodes. The study was limited to a single center, which may affect the generalizability. Children might also have presented to receive care in another facility post-DAMA.